1994
DOI: 10.1207/s15328023top2104_9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Success in the Undergraduate Psychology Major

Abstract: Ball State U?~iversity Tranmipt data were compiled on 288 recent colkge graduates maoring in psychology to determine tk umiables that correlated best with grade point average in psychology (PSYGPA). T k graduates were a highly diverse group in r m of high school academic backgrounds, grades in high schwl, and Schohtic Aptitude Test scores. Factor analysis of 26 predictor variables revealed three clusters of umiables: high school gracksluerbal, general studies, and m a r h t i c s . Multiple regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although 76,000 baccalaureate degrees in psychology are awarded every year (Kuther & Morgan, 2007), the reasons for choosing psychology are unclear, especially because an undergraduate degree in psychology does not lend itself to a professional career as a psychologist. Research on reasons for studying psychology or pursuing the major include a myriad of themes relating to interest in specific careers, academic strengths of students (Meeker, Fox, & Whitley, 1994), impact of gender roles (McCray, King, & Bailly, 2005;Metzner, Rajecki, & Lauer, 1994;Pion et al, 1996), and personality variables such as empathy (Harton & Lyons, 2003) or openness to experience (Marrs, Barb, & Ruggiero, 2007).…”
mentioning
confidence: 99%
“…Although 76,000 baccalaureate degrees in psychology are awarded every year (Kuther & Morgan, 2007), the reasons for choosing psychology are unclear, especially because an undergraduate degree in psychology does not lend itself to a professional career as a psychologist. Research on reasons for studying psychology or pursuing the major include a myriad of themes relating to interest in specific careers, academic strengths of students (Meeker, Fox, & Whitley, 1994), impact of gender roles (McCray, King, & Bailly, 2005;Metzner, Rajecki, & Lauer, 1994;Pion et al, 1996), and personality variables such as empathy (Harton & Lyons, 2003) or openness to experience (Marrs, Barb, & Ruggiero, 2007).…”
mentioning
confidence: 99%
“…Meeker, Fox, and Whitley (1994) studied 288 psychology graduates from Ball State University and found that the best predictors of psychology OPA were grades in introductory psychology, general studies course work, and mathematics (including statistics), which accounted for 67% of the variance in their sample. Shepperd (1993) found that a discriminant function prediction model, based on grade in introductory psychology plus first semester OPA to predict psychology OPA at graduation, correctly classified 82.4% of cases in a sample of 342 Holy Cross University graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Neither Meeker et al (1994) nor Shepperd (1993) considered the impact of gender in their prediction models. If one assumes that their samples consisted of about two-thirds women, it would have been valuable if they could have established that their models were equally valid for women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the scholarship of teaching and learning has demonstrated that faculty are interested in understanding their students' learning techniques. Some disciplines, including sociology, finance, and psychology, have already begun to investigate student perceptions of success and learning among their undergraduate majors (e.g., McKinney, 2005McKinney, , 2008Meeker, Fox, & Whitley, 1994;Paulsen & Gentry, 1995). Such an understanding of these student perceptions can be used to inform pedagogy in areas of course content and approach, better allowing for the instructor to connect to the students, tailor the learning environment to suit student needs, and provide a more enriching learning experience.…”
mentioning
confidence: 99%